Pre-designed consent forms for total hip replacement, total knee replacement, and caesarean section: A national observational study of current English practice. Issue 4 (August 2019) - Light, Alexander; Gupta, Tanya; Nandakumar, Madura; Dadabhoy, Maria; Burrows, Abigail; Daniel, Allen; Karthikeyan, Sandeep
Abstract: Background: Pre-designed procedure-specific consent forms (PCFs) have potential advantages over handwritten forms for improving the consent process and disclosing material risks, as necessitated by the 2015 ' Montgomery ' ruling. We aimed to assess the use and quality of English NHS Trust PCFs for total hip replacement (THR), total knee replacement (TKR), and caesarean section (CS). Methods: All 233 English NHS Trusts were sent a Freedom of Information request seeking PCFs for these operations. Listed risks, and whether their incidence was quoted, were compared against those listed in published PCFs from the British Orthopaedic Association (BOA) and the Royal College of Obstetricians and Gynaecologists (RCOG). Results: 203/233 (87.1%) Trusts responded, contributing 17 THR PCFs, 15 TKR PCFs, and 33 CS PCFs. Overall, the type of risks listed for each operation was highly variable. 5.9% of THR PCFs contained all 18 BOA-quoted risks. No TKR PCF contained all 19 BOA-quoted risks. 24.2% of CS PCFs contained all 17 RCOG-quoted risks. For each operation, few PCFs listed incidences for quoted-risks. Conclusions: Very few Trusts use PCFs for these common operations. When PCFs are used, the reporting of risks and their likelihood is variable and insufficient. BOA- and RCOG-approved PCFs are high quality and influential on Trust-PCF design but still omit important risks. We fear PCFs analysed here do not sufficiently improve the consent process compared to handwritten forms. PCFs have potential to improve the quality of consent, however they need greater uptake and to be of greater quality. Highlights: PCFs have potential advantages over handwritten forms for improving consent. Very few Trusts use PCFs for total hip or knee replacement, and caesarean section. When PCFs are used, the reporting of risks and their likelihood is insufficient. The PCFs here do not sufficiently improve the consent process. PCFs need greater uptake and to be of greater quality.